The Democratisation of Islamic Education: A Study of Two Islamic Schools in Central Java - Khunaifi, Agus; Sarasati, Ruruh (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
The shift in the democratization of education has been influenced by the decentralization of education in Indonesia since 2001. The shift in the dominance of education management from centralized to decentralized can also be seen within Islamic educational institutions. Democracy can be seen, among others, by applying the concept of community-based education in a national education administration organized by Islamic institutions. Data were obtained through interviews, participatory observation and document study. Interviews were conducted with key informants: the principal, teachers, parents, students and the user community. The characteristics of democratization in Islamic schools generally begin with a dialogue between democracy and Islamic teachings. The acceptance of democracy in Hj Isriati's institution is understood as a concept that aligns with Islamic teachings (humanistic model). The acceptance of democracy in Al-Azhar school can be classified into integralistic democratization. Democratization in Islamic schools in Semarang city in managerial aspects is generally based on competitive and professional aspects. This is because Islamic schools are private schools whose funding sources are mostly from the stockholder community, which demands high competition and professionalism to exist in the community. Democratization in the aspect of learning in Islamic schools is generally based on Islamic characteristics and becomes the most prominent feature in democratization in the aspect of learning.